Sir William Stirling Maxwell : scholar of Spanish Art - Macartney, Hilary (Espacio Tiempo y Forma. Serie VII, Historia del Arte, 1999)
Este artículo tiene el propósito de aumentar la escasa información ya publicada sobre Sir William Stirling Maxwell (1808-1878), y de considerar si son justas las opiniones que sobre el se han expresado. Estudia las traducciones de sus obras al castellano incluso el proyecto para una versión española de los Annals of the Artists of Spain. Se enfoca en algunos aspectos de sus primeras visitas a España, especialmente su romanticismo al principio y su pronto rechazo del mito orientalista de España que promulgaban muchos escritores británicos, como Richard Ford. No obstante, Stirling y Ford terminaron por ser grandes amigos durante las últimas etapas de la preparación de los Annals. A partir de 1847, Stirling podía libremente satisfacer su afición al coleccionismo de arte y libros. The aims of this article are to add to the little information already published on Sir William Stirling Maxwell (1808- 1878) and to examine whether common views of him are fair. It discusses Spanish translations of his works, including the project for a Spanish edition of the Annals of the Artists of Spain. Some aspects of Stirling's early visits to Spain are highlighted, particularly his initial romanticism and early rejection of the Orientalist view of Spain popular in Britain amongst writers such as Richard Ford. Stirling's friendship with Ford, however, developed during the final stages of preparing the Annals. After his father's death in 1847, Stirling could indulge his love of books and art. Many of the paintings he collected reflected his art historical interests in royal patronage and the status of artists in Spain.